Classroom Action Research Training and Assistance for Science Teachers at Attohiriyah High School, Bodak, Central Lombok - Aris Doyan; Susilawati Susilawati; Muhammad Zuhdi; Ni Nyoman Sri Putu Verawati; Gunawan Gunawan; Hikmawati Hikmawati; Syamsul Hakim; Baiq Hurun Infarlina; Sahwi Sahwi; Fitriana Yuni Hartati (Pascasarjana Universitas Mataram, 2023)
Community service carried out by the service team chose schools as targets for implementing activities. School selection is carried out through initial observations to find out the problems and appropriate solutions. This service activity takes the form of training in preparing Classroom Action Research (CAR). The activities carried out were not only limited to training, but the service team also provided assistance to Attohiriyah Bodak High School teachers, especially natural science subject teachers, namely physics, chemistry and biology teachers. The benchmark for the success of this activity is the participant's response and the follow-up provided after the training. Responses from teachers participating in training and mentoring. Most of them gave positive responses and stated that this activity was very useful for teachers in carrying out or creating scientific work